2016
DOI: 10.1186/s13068-016-0531-0
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and mechanism of cellulase enzymes onto lignin isolated from corn stover pretreated with liquid hot water

Abstract: BackgroundIn the bioconversion of lignocellulosic substrates, the adsorption behavior of cellulase onto lignin has a negative effect on enzymatic hydrolysis of cellulose, decreasing glucose production during enzymatic hydrolysis, thus decreasing the yield of fermentation and the production of useful products. Understanding the interaction between lignin and cellulase is necessary to optimize the components of cellulase mixture, genetically engineer high-efficiency cellulase, and reduce cost of bioconversion. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 39 publications
3
112
0
Order By: Relevance
“…The adsorption data fitted well with the Langmuir isotherm. The maximum adsorptions of CBH were 7.63, 5.53, and 12.32 mg/g for the three lignin fractions, which were similar to the literature (Pareek et al, 2013;Zheng et al, 2013;Machado et al, 2015;Lu et al, 2016;Sun et al, 2016). It should be noted that the binding results could be affected by the different lignin isolation/pretreatment conditions, enzyme and test conditions (temperatures, lignin loading) used for determination.…”
Section: Cbh Adsorption To Lignins By Langmuir Equationsupporting
confidence: 65%
See 2 more Smart Citations
“…The adsorption data fitted well with the Langmuir isotherm. The maximum adsorptions of CBH were 7.63, 5.53, and 12.32 mg/g for the three lignin fractions, which were similar to the literature (Pareek et al, 2013;Zheng et al, 2013;Machado et al, 2015;Lu et al, 2016;Sun et al, 2016). It should be noted that the binding results could be affected by the different lignin isolation/pretreatment conditions, enzyme and test conditions (temperatures, lignin loading) used for determination.…”
Section: Cbh Adsorption To Lignins By Langmuir Equationsupporting
confidence: 65%
“…It is widely accepted that lignin inhibits enzymatic hydrolysis of lignocellulosic biomass (Zeng et al, 2014;Lu et al, 2016;Saini et al, 2016;Yang et al, 2016). The adsorption of enzymes onto isolated lignins from dilute acid or hot water pretreated biomass has been studied (Zheng et al, 2013;Yu et al, 2014;Li et al, 2016;Lu et al, 2016;Sun et al, 2016). They reported key lignin-enzyme binding effects including the effects of condensed phenolic OH groups, methoxy groups, and the degree of lignin condensation on cellulase binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the Benzene-Alcohol Extractive Contents of the WISs During LHW pretreatment, the water extracts were composed primarily of monosaccharides, a small amount of oligosaccharides, and water-soluble polysaccharides (Lu et al 2016). However, some substances could not be extracted with water, such as the terpene compounds, fats, waxes, and tannins.…”
Section: Changes In the Glucose And Xylan Content Of The Prehydrolysatesmentioning
confidence: 99%
“…Several reports have shown that the chemical and physical structures of lignin have a notable function in determining the magnitude of inhibition contributed by lignin to enzymatic hydrolysis (Ko et al 2015;Lu et al 2016). For example, Sewalt et al (1997) demonstrated that increasing the phenolic hydroxyl content of lignin also increases its inhibition activity towards enzymatic hydrolysis.…”
Section: Introductionmentioning
confidence: 99%